The care of patients with special needs in pediatric dentistry - Uchôa, Sue Ann Castro Lavareda; Corrêa, Suelen Castro Lavareda; Corrêa, Davi Lavareda; Corrêa, Vânia Castro (Seven Editora, 2024)
Children with special needs encompass a variety of conditions that require specific medical care, specialized interventions, and the use of adapted services or programs. This definition is applied in an equally crucial way to the context of dental care. This article aims to conduct a literature review on the challenges faced by pediatric dentists when dealing with patients with special needs and to discuss adapted approaches that can be implemented to overcome these complex difficulties. Patients with special needs in pediatric dentistry present unique challenges that require tailored approaches and a comprehensive understanding by professionals in the field. The implementation of strategies, such as behavioral guidance, conscious sedation and multidisciplinary teamwork, emerges as a necessity to offer quality care, ensuring the well-being and oral health of these patients in a holistic way. This complex scenario highlights the importance of a personalized and integrated approach to dental care for children with special needs, aiming not only at the clinical aspect, but also at the quality of life of these patients. The intersection between education, professional training, and adequate support is essential for the success of these adapted approaches. DOI: https://doi.org/10.56238/sevened2023.007-042